Use of technical analysis in FOREX trading - Vítovec, Josef; Žilák, Pavel; Stádník, Bohumil; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2012)
The paper reacts to tremendous increase in popularity of FX trading among retail investors in recent years, caused mainly by easy accessibility through numerous online trading platforms and dramatic fall in trading costs. One of the accompanying trends along with increasing trading speed is a departure from fundamental analysis and shift towards more technical approach. In reaction to that, the paper aims to review the most popular technical trading rules and puts the findings in contrast with existing empirical literature and efficient market hypothesis. Although being far from discovering an ultimate trading formula, the paper concludes that selected trading strategies do demonstrate a certain degree of predictability of future exchange rate movements.
Vedoucí práce: Pavel Žilák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor dipl. práce]; diplomové práce; master's theses